THE APPLICATION OF DIVERSION IN THE INVESTIGATION OF CRIMINAL OFFENCES IN THE FIELD OF TRAFFIC AGAINST CHILDREN - Reimon Supusepa; Elias Zadrach Leasa (Faculty of Law, Universitas Pekalongan, 2025)
Restorative justice is a diversion process in which all parties involved in a particular criminal offence together solve problems, create an event to make things better by involving child victims, children and the community in finding solutions to repair, reconciliation and reassurance that are not based on revenge. The purpose of this study is the application of diversion in the investigation of criminal offences in the field of traffic against children and the application of diversion by investigators has been effective to be able to handle children as perpetrators of criminal offences in the field of traffic. The research method used is normative juridical research method. The Police in order to provide protection to Children Against the Law through the discretionary authority granted by the law have made various best efforts in handling child criminal cases as a whole and this can be seen from the various child criminal cases that can be resolved through the concept of restorative justice or through diversion and various rules / guidelines made to support the implementation of handling child crimes.